The impact of ultrasonic parameters on the exfoliation of NiFe LDH nanosheets as electrocatalysts for the oxygen evolution reaction in alkaline media - Tshimangadzo S. Munonde; Haitao Zheng (Ultrasonics Sonochemistry, 2021)
The ultrasonic process has been examined to exfoliate layered materials and upgrade their properties for a variety of applications in different media. Our previous studies have shown that the ultra-sonication treatment in water without chemicals has a positive influence on the physical and electrochemical performance of layered materials and nanoparticles. In this work, we have probed the impact of ultrasonication on the physical properties and the oxygen evolution reaction (OER) of the NiFe LDH materials under various conditions, including suspension concentration (2.5–12.5 mg mL−1), sonication times (3–20 min) and amplitudes (50–90%) in water, in particular, sonication times and amplitudes. We found that the concentration, amplitude and time play significant roles on the exfoliation of the NiFe LDH material. Firstly, the NiFe LDH nanosheets displayed the best OER performance under ultrasonic conditions with the concentration of 10 mg mL−1 (50% amplitude and 15 min). Secondly, it was revealed that the exfoliation of the NiFe LDH nanosheets in a short time (<10 min) or a higher amplitudes (≥80%) has left a cutdown on the OER activity. Comprehensively, the optimum OER activity was displayed on the exfoliated NiFe LDH materials under ultrasonic condition of 60% (amplitude), 10 mg mL−1 and 15 min. It demanded only 250 mV overpotentials to reach 10 mA cm−2 in 1 M KOH, which was 100 mV less than the starting NiFe LDH material. It was revealed from the mechanism of sonochemistry and the OER reaction that, after exfoliation, the promoted OER performance is ascribed to the enriched Fe3+ at the active sites, easier oxidation of Ni2+ to Ni3+, and the strong electrical coupling of the Ni2+ and Fe3+ during the OER process. This work provides a green strategy to improve the intrinsic activity of layered materials.